Poesia visual brasileira no contexto de crise - Borsato, Fabiane Renata [UNESP]; Buoro, Thiago [UNESP] (My University, 2013)
In this project, we tried to analyze, in a very short way, the relations between Brazilian Visual Poetry and a phenomenon in modern literature known as crises of the verse. In sequence, we tried to situate this poetry in a provisory category which the current criticism sees it as the contemporary Brazilian poetry. For sure, the Concretism and its esthetics deployments assured space for the visually in poetry.

Procuramos aqui analisar brevemente as relações da poesia visual brasileira com o fenômeno na literatura moderna conhecido como crise do verso. Depois buscamos situar essa poesia dentre as categorias provisórias por meio das quais a crítica atual pensa a poesia brasileira contemporânea. Sem dúvida, o Concretismo e seus desdobramentos estéticos garantiram espaço para a visualidade em poesia.
Keywords: Visual poetry; Concretism; Contemporary Brazilian poetry; Poesia visual; Concretismo; Poesia brasileira contemporânea